The Effects of Losing a Business Group Affiliation. (16th November 2018) - Larrain, Borja; Sertsios, Giorgo; Urzúa I, Francisco
Abstract: We propose a novel identification strategy for estimating the effects of business group affiliation. We study two-firm business groups, some of which split up during the sample period, leaving some firms as stand-alone firms. We instrument for stand-alone status using shocks to the industry of the other group firm. We find that firms that become stand-alone reduce leverage and investment. Consistent with collateral cross-pledging, the effects are more pronounced when the other firm had high tangibility. Consistent with capital misallocation in groups, the reduction in leverage is stronger in firms that had low (high) profitability (leverage) relative to industry peers. Received July 3, 2017; editorial decision April 7, 2018 by Editor Wei Jiang. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.